2001
DOI: 10.1143/jjap.40.6496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ni Doping on Improvement of the Tunability and Dielectric Loss of Ba0.5Sr0.5TiO3 Thin Films for Microwave Tunable Devices

Abstract: The structural, microstructural, and surface morphological properties of Ba 0.5 Sr 0.5 TiO 3 thin films were investigated as a function of Ni dopant concentration. The Ni-dopant concentration in BST films has a strong influence on the material properties including dielectric and tunable properties as well as film growth rate. Ni doped (≤3 mol%) BST films showed denser, smoother, and smaller grain sizes than those with 6 and 12 mol% Ni. Dielectric constant and loss of 3 mol% Ni-doped BST films were about 980 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…To date, several group's researches have shown that the additions of some dopants (with small concentrations) such as Fe 2ϩ , Mn 2ϩ , Mg 2ϩ , Ni 2ϩ , and La 3ϩ into pure BST thin films could dramatically reduce the dielectric-loss tangent of BST thin films. [65][66][67][68][69][70][71][72][73][74] The Mg-doping (1 mol.%) has the greatest effect on reducing the dielectric-loss tangent of (Ba 0.6 Sr 0.4 )TiO 3 films at microwave frequencies while retaining useful dielectric tunability and insulating properties compared with the pure (Ba 0.6 Sr 0.4 )TiO 3 thin films. [69][70][71] The mechanism for lowering the dielectric loss by addition of some dopants centers on the thesis that ions with a charge less than 4 ϩ can substitute for Ti 4ϩ and behave as electron acceptors.…”
Section: Technical Challenges and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several group's researches have shown that the additions of some dopants (with small concentrations) such as Fe 2ϩ , Mn 2ϩ , Mg 2ϩ , Ni 2ϩ , and La 3ϩ into pure BST thin films could dramatically reduce the dielectric-loss tangent of BST thin films. [65][66][67][68][69][70][71][72][73][74] The Mg-doping (1 mol.%) has the greatest effect on reducing the dielectric-loss tangent of (Ba 0.6 Sr 0.4 )TiO 3 films at microwave frequencies while retaining useful dielectric tunability and insulating properties compared with the pure (Ba 0.6 Sr 0.4 )TiO 3 thin films. [69][70][71] The mechanism for lowering the dielectric loss by addition of some dopants centers on the thesis that ions with a charge less than 4 ϩ can substitute for Ti 4ϩ and behave as electron acceptors.…”
Section: Technical Challenges and Perspectivesmentioning
confidence: 99%
“…62 dopants must be optimized to obtain the best overall properties for use in tunable devices applications. [72][73][74] It should be kept in mind that good dielectric and insulating properties are not standalone requirements, other material properties, such as film structure, microstructure, surface morphology, and the nature of the film/substrate interface, also affect device performance and long-term reliability. Therefore, to fully evaluate and understand the properties stated previously, the influence of acceptor concentration on the microstructural, surface morphological, and interfacial properties must be assessed and correlated with the films' dielectric and insulating properties.…”
Section: Technical Challenges and Perspectivesmentioning
confidence: 99%
“…Some dopants including Ni 2+ , Fe 2+ , Fe 3+ , Mn 2+ , Mn 3+ , Co 2+ , Co 3+ , Cr 3+ , and Bi 3+ etc. which can occupy the B sites of the (ABO 3 ) perovskite structure and behave as electron acceptors, have been known to lower dielectric loss [3][4][5][6][7][8][9][10][11][12]. At the same time, the dielectric loss of BST also can be dramatically decreased by adding some low-loss and low-K oxides, such as MgO [13,14], Al 2 O 3 [11] and SiO 2 [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…6 [18]. Chen et al [19] reported the electric properties of La/Mg Co-doped (Ba 0.7 Sr 0.3 )TiO 3 thin films.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major challenges encountered for realizing the integration of BST thin films into electrically tunable devices is the simultaneous minimization of the dielectric loss and maximization of dielectric tunability. Many attempts to improve the dielectric properties of BST thin films have focused on film texturing, 5 improvement of the dielectric-electrode interface, control of film stress, 6,7 addition of acceptor dopants, [8][9][10] and modification of the film microstructures. 11 Almost no attempt has successfully improved the dielectric tunability and dielectric loss simultaneously.…”
mentioning
confidence: 99%